ANALISIS KESALAHAN NUMERASI SISWA SMA DALAM MENYELESAIKAN SOAL-SOAL AKM POKOK BAHASAN LOGARITMA - Sari, Desi Vita; Suryadi, Didi; Nurjanah, Nurjanah (PHI: Jurnal Pendidikan Matematika, 2024)
This study was conducted with the aim of knowing the numeracy errors of high school students in working on logarithm problems on the Minimum Competency Assessment (AKM). The method used in this research is a qualitative approach. The research instrument is a numeracy test in the form of multiple choice questions, short form, descriptions with three indicators and guided interviews. The research subjects consisted of 6 grade 10th subjects at one of the public high schools in Bandung. The results showed that students' numeracy skills were still relatively low. A total of 5 students were categorized as low and 1 subject was categorized as medium. The lowest score obtained was 27 and the highest was 44. Based on the results of the interview, it was found that students were lazy to read the questions because the questions were so long, the processing time went so fast, and had a low understanding of the concept of logarithm material, so they had difficulty in overcoming he numeracy problems of the Minimum Competency Assessment (AKM).